Regulation of the Activities of the Real Estate Agencies in Bulgaria - Tomova, Doroteya (Research Papers, 2018)
The article presents the current regulation of real estate agencies in Bulgaria. A comparison between the Bulgarian Commercial Law, the European Standard "Real Estate Brokerage Services" and the legal framework for the activity of brokers in real estate transactions in Slovenia. The purpose of the article is to draw on some of the shortcomings of the Bulgarian legislation and of the activities of the Bulgarian real estate agencies, based on the examined practices. Recommendations for changes in the legal framework and for the implementation of the appropriate foreign good practices according to the author were formulated.
Keywords: Real estate agencies; Mediation; Rule